2023
DOI: 10.1007/s13659-023-00377-0
|View full text |Cite|
|
Sign up to set email alerts
|

Uncarialines A-E, new alkaloids from Uncaria rhynchophylla and their anticoagulant activity

Abstract: Uncarialines A-E (1–5), five undescribed monoterpene indole alkaloids, together with five known analogues were obtained from the stems of Uncaria rhynchophylla. Alkaloids 1–3 were unique 3,4-seco-tricyclic alkaloids with a 6/5/10 ring system, while 4 and 5 possessed a rare rearranged scaffold originated from corynantheine-type alkaloids with C-2/C-7 oxidation. Their structures were characterized by a comprehensive analysis of MS, NMR, and ECD. Their effects on blood clotting times of human plasma were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], it was reported that the original version of this article unfortunately contained a mistake. Prof. Hong-Ping He is also one of the corresponding authors.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], it was reported that the original version of this article unfortunately contained a mistake. Prof. Hong-Ping He is also one of the corresponding authors.…”
mentioning
confidence: 99%